Physical Vapor Deposited Thin Films of Lignins Extracted from Sugar Cane Bagasse: Morphology, Electrical Properties, and Sensing Applications - Volpati, Diogo [UNESP]; Machado, Aislan D. [UNESP]; Olivati, Clarissa A. [UNESP]; Alves, Neri [UNESP]; Curvelo, Antonio A. S.; Pasquini, Daniel; Constantino, Carlos J. L. [UNESP] (Amer Chemical Soc, 2011)
The concern related to the environmental degradation and to the exhaustion of natural resources has induced the research on biodegradable materials obtained from renewable sources, which involves fundamental properties and general application. In this context, we have fabricated thin films of lignins, which were extracted from sugar cane bagasse via modified organosolv process using ethanol as organic solvent. The films were made using the vacuum thermal evaporation technique (PVD, physical vapor deposition) grown up to 120 nm. The main objective was to explore basic properties such as electrical and surface morphology and the sensing performance of these lignins as transducers. The PVD film growth was monitored via ultraviolet-visible (UV-vis) absorption spectroscopy and quartz crystal microbalance, revealing a linear relationship between absorbance and film thickness. The 120 nm lignin PVD film morphology presented small aggregates spread all over the film surface on the nanometer scale (atomic force microscopy, AFM) and homogeneous on the micrometer scale (optical microscopy). The PVD films were deposited onto Au interdigitated electrode (IDE) for both electrical characterization and sensing experiments. In the case of electrical characterization, current versus voltage (I vs V) dc measurements were carried out for the Au IDE coated with 120 nm lignin PVD film, leading to a conductivity of 3.6 x 10(-10) S/m. Using impedance spectroscopy, also for the Au IDE coated with the 120 nm lignin PVD film, dielectric constant of 8.0, tan delta of 3.9 x 10(-3)) and conductivity of 1.75 x 10(-9) S/m were calculated at 1 kHz. As a proof-of-principle, the application of these lignins as transducers in sensing devices was monitored by both impedance spectroscopy (capacitance vs frequency) and I versus time dc measurements toward aniline vapor (saturated atmosphere). The electrical responses showed that the sensing units are sensible to aniline vapor with the process being reversible. AFM images conducted directly onto the sensing units (Au IDE coated with 120 nm lignin PVD film) before and after the sensing experiments showed a decrease in the PVD film roughness from 5.8 to 3.2 nm after exposing to aniline.